E-Commerce Bibliometric Analysis in Business Development - Dzakirah, Nasya Rabbi; Cesoria Ola, Yola Zerlinda (Westscience Press, 2024)
E-commerce is the way individuals buy and sell goods and services through the Internet. E-commerce is part of a larger business sector, covering everything from trade to running workflows, working with business partners, providing customer service, and more. The study aims to study the use of bibliometrics in e-commerce business development and VOSviewer as an analytical tool. The amount of metadata from twenty pieces of documentation that were successfully collected suggests that many authors are associated with this research. Overall, research on e-commerce during the development of new e-commerce provides a good reference point for further bibliometric research.